HAK OPORTUNITAS JAKSA DALAM MENYIKAPI PENGADUAN KASUS PERZINAHAN - Shidarta Shidarta (Jurnal Yudisial, 2011)
ABSTRACTIn the case of adultery occurred in Mataram, the public prosecutor used the right of discretion as not to accuse the complainant's wife. The use of this right has afterward become a polemic pertaining to the interpretation of crime by complaint in the context of adultery and the right of discretion as contained in the formulation of Article 284 paragraph (1) and (5) of the Criminal Code, and Article 35 of Law on the Attorney of the Republic of Indonesia. The author of this article argues that the use of right of discretion undermines the legality principle which is still highly respected in the enforcement of criminal law. Therefore, this right must be used very carefully. And the Attorney General who should have the authority of discretionary in deciding the suitability the use of the right of discretion. Keywords: the right of discretion, prosecution, adultery, crime by complaint. ABSTRAKDalam kasus perzinahan yang terjadi di Semarang, JPU menggunakan hak oportunitasnya untuk tidak menuntut isteri terdakwa. Penggunaan hak demikian tetap menjadi polemik berkenaan dengan penafsiran delik aduan dalam tindak pidana perzinahan dan hak oportunitas sebagaimana diformulasikan dalam Pasal 284 ayat (1) dan (5) KUHP dan Pasal 35 UU Kejaksaan RI. Penulis artikel ini setuju bahwa penggunaan hak oportunitas ini harus tetap dihormati dalam penerapan hukum pidana, dan oleh karena itu harus pula dipakai secara ekstra berhati-hati. Jaksa Agunglah yang memiliki kewenangan untuk menetapkan kelayakan penggunaan hak tersebut. Kata kunci: hak oportunitas, tuduhan, perzinahan, delik aduan.